The Effectiveness of Human Rights Mediation By The National Commission of HAM After The Issuance of The National Commission of HAM Regulation No. 2 of 2025 - Putri, Dyah Maharani (Ilmu Hukum Prima (IHP), 2026)
Komnas HAM Regulation No. 2 of 2025 is an important breakthrough that updates the guidelines for human rights (HR) mediation in Indonesia, optimizing dispute resolution through three main stages: pre-mediation (fact verification and party readiness), core mediation (consultation, negotiation, and conciliation), and post-mediation (drafting an agreement deed that can be registered with the district court). This research analyzes the effectiveness of implementing the regulation after its publication in February 2025, focusing on increasing the authority of the National Human Rights Commission (Komnas HAM) mediators, inter-agency synergy such as with the Ministry of Law and Human Rights, and the challenges of executing binding mediation agreements. A normative legal approach is used to evaluate secondary data from official reports, legal journals, and empirical cases. The research results show a significant procedural improvement, such as the win-win solution principle and independent expert assessment, which accelerates the process compared to conventional litigation mechanisms. However, structural challenges remain, including political resistance from corporations, a lack of enforcement commitment by law enforcement agencies, and limited human resources, resulting in a mediation success rate of only about 40% out of a total of 1,737 complaints of alleged human rights violations in the corporate sector during the 2024-2025 period. Urgent reforms are needed, such as strengthening the subpoena power of the National Human Rights Commission and digital integration for monitoring agreements, to strengthen the role of this institution in creating conducive conditions for the sustainable implementation of human rights.